Factors associated with postoperative dysphagia in older adults with hip fracture: a scoping review - Huang, Ganying; Zhou, Yitao; Yang, Huijie; Zhou, Tao; Zhou, Yangbin; Sun, Qiuhua (Frontiers in Surgery, 2026)
BackgroundPostoperative dysphagia is increasingly recognized as a common but underdiagnosed complication in older adults undergoing hip fracture surgery, and is associated with adverse outcomes such as aspiration pneumonia, malnutrition, prolonged hospitalization, and delayed rehabilitation. However, evidence regarding its reported incidence and influencing factors remains fragmented and heterogeneous.ObjectiveThis scoping review aimed to map the existing evidence on the incidence, assessment methods, and factors associated with postoperative dysphagia in older adults undergoing hip fracture surgery, and to identify knowledge gaps relevant to perioperative management and rehabilitation.DesignThis study was designed as a scoping review to map the existing evidence on postoperative dysphagia in older adults undergoing hip fracture surgery. The review was conducted in accordance with the Arksey and O'Malley framework and reported following the PRISMA-ScR guidelines.MethodsA comprehensive search was performed across nine English and Chinese databases from inception to June 2025. Studies invovling patients aged ≥ 60 years undergoing hip fracture surgery were included.Risk of bias assessment and descriptive quantitative synthesis were applied to characterize the heterogeneity of the evidence, rather than to generate definitive estimates.ResultsEleven studies were included. Six types of swallowing assessment methods were identified, ranging from bedside screening to videofluoroscopic swallowing studies. The reported incidence of postoperative dysphagia varied widely across studies. A descriptive quantitative synthesis yielded a pooled prevalence of 39% (95%CI:0.26–53); however, this estimate should be interpreted with caution due to extreme statistical heterogeneity (I2 = 99%) and variations in assessment timing. Influencing factors were grouped into patient-related, surgery-related, and sarcopenia-related domains. Evidence linking sarcopenia to persistent postoperative dysphagia was limited.ConclusionsPostoperative dysphagia in older adults with hip fracture is a multifactorial condition with a widely varying and inconsistently reported incidence. Differences in assessment methods and timing contribute substantially to heterogeneity across studies. Future research should focus on longitudinal recovery trajectories and the role of sarcopenia to inform targeted perioperative and rehabilitation interventions.Systematic Review Registrationhttps://doi.org/10.17605/OSF.IO/4NR9H.